GTrust: Group Extension for Trust Models in Distributed Systems - Robson de Oliveira Albuquerque; Luis Javier García Villalba; Tai-Hoon Kim (International Journal of Distributed Sensor Networks)
This paper proposes and describes a trust model for distributed systems based on groups of peers. A group is defined as a collection of entities with particular affinities and capabilities. All entities may have a trust and a reputation value of each other in the system. In many cases it may be necessary to trust the whole system instead of one particular entity. In such cases group trust represents the trust of their particular members. To achieve this, this paper presents a group trust calculation model. We implemented the proposed model in a P2P simulation tool and presented main results for group trust calculation.